Capsular Contracture, Prolonged Use of Breast Implants with Pleural Effusion: a Case Report - Moenadjat, Yefta (UI Scholars Hub, 2020)
A case with prolonged implanted breast prosthesis experienced a prolonged capsular contracture complicated with pleural effusion. A complete capsular removal proceeded instead of removal of the prosthesis solely. The present case aimed to share experiences that may add to the scientific horizon regarding the rare complications of breast prosthesis and rarely reported.